Comparative study on reproductive compatibility of two geographic populations of Diadromus collaris (Gravenhors) (Hym.: Ichneumonidae), a pupal parasitoid of Plutella xylostella (L.) (Lep.: Plutellidae) - SHI Zu-hua; LIU Shu-sheng; GEBREMESKEL Fisseha B. (浙江大学学报. 农业与生命科学版, 2002)
Comparative study on reproductive compatibility was conducted in laboratory between two geographic Diadromus collaris populations, one originated from Hangzhou, Zhejiang and the other from Lishan, Taiwan, China, by both mass mating and single-pair mating cross, and back cross breeding experiments using the pupae of Plutella xylostella as hosts. Number of host pupae parasitized, number of progeny produced per female and sex ratio of progeny in all cross and back cross combinations were compared. The sex ratio of the population from Lishan was significantly lower than that of population from Hangzhou in mass mating cross, and the sex ratio in the combination between hybrid female produced from the cross (female of Lishan population and male of Hangzhou population) and male from Hangzhou population was significantly lower than that in the combination between female of Hangzhou population and the hybrid male produced from the cross (female of Hangzhou population and male of Lishan population) in a back cross. However, no significant differences have been detected in all other biological characteristics tested between all other cross and back cross combinations. The results show that the two geographic populations of the parasitoid still remain reproductively compatible, do not have reproductive isolation, and keep a well-defined species.